Experimental Study of the Crack Growth in Stainless Steels Using Thermal Methods. (2015) - Palumbo, D.; Ancona, F.; De Finis, R.; Galietti, U.
Abstract: Martensitic steels are used in the engineering fields where high temperatures, corrosive environments and high mechanical stress are required. In this work, theThermoelastic Stress Analysis (TSA) technique was used to characterize the fracture mechanics behaviour of twomartensitic stainless steels. TSA technique is proposed both for the monitoring in continuous way the crack position and for evaluatingthe stress intensity factor (SIF). An automatic procedure was developed capable to process very quickly the thermoelastic data acquired during the test. In this way, the Paris' Law can be assessed reducing significantly the testing time.